Comparative phylogeography of two codistributed endemic cyprinids in southeastern Taiwan. (February 2017) - Chiang, Tzen-Yuh; Chen, Yi-Yen; Lee, Teh-Wang; Hsu, Kui-Ching; Lin, Feng-Jiau; Wang, Wei-Kuang; Lin, Hung-Du
Abstract: Two cyprinid fishes, Spinibarbus hollandi and Onychostoma alticorpus, are endemic to southeastern Taiwan. This study examined the phylogeography of these two codistributed primary freshwater fishes using mitochondrial DNA cytochrome b sequences (1140 bp) to search for general patterns in the effect of historical changes in southeastern Taiwan. In total, 135 specimens belonging to these two species were collected from five populations. These two codistributed species revealed similar genetic variation patterns. The genetic variation in both species was very low, and the geographical distribution of the genetic variation corresponded neither to the drainage structure nor to the geographical distances between the samples. The results of a statistical dispersal-vicariance analysis suggested that the ancestral populations of these two species were distributed in southern Taiwan before their dispersal. Our study suggests that the initial colonization occurred in the Kaoping River followed by eastern and northward dispersal. Our results also indicate that the Central Range in Taiwan did not act as a barrier to the dispersal of S. hollandi or O. alticorpus . Graphical abstract: Highlights: The phylogeography of S. holandi and O. alticorpus were very similar. Two species both displayed the initial colonization was hypothesized to be in Kaoping River. Central Range within Taiwan did not act as a barrier to the dispersal of S. holandi and O. alticorpus.